Monitoring Progess for Toddler Case Handling Malnutrition With Spatial Information Systems in Banda Aceh - Tarmizi Tarmizi (Jurnal Sistem Informasi Kesehatan Masyarakat, 2016)
ABSTRACTNutrition problem contributes to the death rate of toddler. In Aceh Province during 2013,  there are 855 toddlers suffering malnutrition and only 14,04% of them recovered, 2,46% died and there are still 714 more toddlers under treatment.Qualitative descriptive research with observational design through action research approach using  Geographical Information System (GIS) are carried out in the city of Banda Aceh where the sample of children with malnutrition are obtained from the result of nutrient status monitoring, weighing routine data in posyandu, investigation of the health facilities and the report from society. The collected dependent data variables are children with severe malnutrition and malnourished children, the residence location of the research subjects, the work place of the nutrient management employee, the community health center (puskesmas) and serving fasilities of children with severe malnutrition by Global Positioning System (GPS).The distribution pattern and regions prone to children with malnutrition are concentrated in Kecamatan Kuta Raja, Kecamatan Meuraxa and Kecamatan Ule Kareng. In those districts, the number of children with severe malnutrition is above 0,6% and the number of malnourished children is also above 1,5% of the minimum tolerance number of children set by the City Health Department of Banda Aceh. The percentage of the weighed children to the number of target (D/S) for those districts is in between 53,7% to 69,5%. The number of recovered children after being treated is 7,2%, while 0,9% are died and 9,9% of the children with severe malnutrition are dropped out.  The number and the distribution of nutrient management employee are not sufficient and they are not well trained with 21,2% of the posyandu are active. In the other hand, the number and the distribution of puskesmas and hospital are fairly equally distributed throughout Banda Aceh. The development of severe malnutrition children monitoring management information system creates the information of improvement of children with severe malnutrition, distribution map of nutritional cases, the distribution of human resources and the health facilities, and produces a report of success coverage of nutritional program indicator.The distribution pattern and regions prone to malnutrition are distributed in the coastal area and in the city border which are slum and poor region. The regions also suffer low quantity and quality of nutrient officer, limited operational infrastructure, and only few posyandu are active . The severe malnutrition children monitoring management information system can help through evaluating the improvement of the children’s recovery and it can also produce various information needed. Keywords: Spatial information system, improvement monitoring, toddler, severe malnutrition